The Renovo Story: Venture Capital at the Cutting Edge - Barnes, Simon (Senate Hall, 2004)
The case explores the creation and venture capital financing of Renovo, a biotechnology start up created in 2000 at the University of Manchester, UK. The case examines a variety of issues central to the creation of university spin outs from both the entrepreneur's and the VC's perspective, with the overall goal of constructing a deal acceptable to all parties. In a broader context, the case illustrates the notion of milestone-based financing for venture capital-backed technology start-ups.
Keywords: biotechnology|venture capital|entrepreneurship|university|spin out